Answer :

(i) p(x) = 4x2 – 5x + 3


p(0) = 4(0)2 – 5(0) + 3


p(0) = 0– 0 + 3


p(0) = 3


(ii) p(x) = 4x2 – 5x + 3


p(-1) = 4(-1)2 – 5(-1) + 3


p(-1) = 4 × 1– (-5) + 3


p(-1) = 4 +5 + 3


p(-1) = 12


(iii) p(x) = 4x2 – 5x + 3


p(2) = 4(2)2 – 5(2) + 3


p(2) = 4 × 4– 10 + 3


p(2) = 16– 10 + 3


p(2) = 9


(iv) p(x) = 4x2 – 5x + 3







Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Find p(0), p(1) aAP- Mathematics

Write whether theAP- Mathematics

Classify the follAP- Mathematics

Verify whether thAP- Mathematics

Verify whether thAP- Mathematics

Verify whether thAP- Mathematics

Write the coefficAP- Mathematics

Give one example AP- Mathematics

Verify whether thAP- Mathematics

Verify whether thAP- Mathematics